Monopol handlu zagranicznego w gospodarce socjalistycznej (na tle międzynarodowych stosunków ekonomicznych): [Foreign trade monopoly in socialist economy (in the light of international economic relations)] (Studia Prawnicze / The Legal Studies, 1967)
Approaching the problem of monopoly in foreign trade, particular attention is given to the essence of such institution in a socialist country in which such a monopoly is indispensable subject of planned economy in an organism founded in socializing of means of production. The nature of foreign trade monopoly is discussed on the backround of mutual relations between socialist and Western countries. From the point of view of development of such .relations the author polemizes with the objections interposed in Western doctrine as regards the theory and branches of the socialist foreign trade.